Isolated and multiple causes of equine dystocia - Ellerbrock, Markus; Krohn, Judith; Büttner, Kathrin; Wehrend, Axel; Justus Liebig University Giessen (My University, 2024)
Background: Dystocia is rare in horses, but is life-threatening for mares and foals. Therefore, veterinary research depends on up-to-date data to optimise equine dystocia management. In addition, knowledge of the prognosis of equine dystocia is necessary to advise animal owners. This retrospective study of equine dystocia aimed to enrich existing datasets with up-to-date information. For the first time, the focus was on the causes of dystocia that occurred alone or in combination. Over a period of 10 years, 72 cases of dystocia were analysed using a standardised, predetermined diagnosis code. Results: Of the 72 cases of dystocia, an isolated cause of dystocia was identified in 37 cases (51.4%) and 35 mares showed a combination of two or more causes (48.6%). Foetal causes were significantly more frequent origin of dystocia (66/69) than maternal causes (3/66) (P < 0.0001). Incorrect posture of the foetal forelimbs and head was the most common combination at 25.7%. The most common isolated cause of dystocia was incorrect posture of the foetal forelimbs (18.9%). A foetotomy was performed in 68% of cases. A caesarean section or an extraction was performed in 13.9% of the cases. Three mares died before any obstetric care was provided. Nine mares (12.5%) were not discharged alive. 73 foals were delivered of which 55 were already dead before veterinary treatment began. In relation to the total number of births in which the foetus was alive at the start of obstetric care, the foetal mortality rate was 61.1% and 88.9% by the time the mare was discharged. Conclusions: It has been demonstrated for the first time that multiple causes of dystocia in horses are almost as common as isolated causes of dystocia. Neonatal mortality remains high, indicating that the timely detection and treatment of dystocia has the highest priority.
Keywords: ddc:630